Feasibility Analysis of “KAOSI” the Graphic Art T-shirt - Ayu Anggraeni Sibarani; Indro Prakoso; Dewi Tria Setyaningrum; Sri Ambarwati (JIE Scientific Journal on Research and Application of Industrial System, 2023)
A business feasibility analysis is necessary to conduct to determine whether a business is viable and to enhance its quality and quantity. The analysis included (1) technical, (2) marketing, (3) management and organizational, and (4) financial. This study uses a business feasibility analysis to determine the viability of new MSME businesses named KAOSI. Based on the research conducted, it has been determined that the KAOSI is considered feasible because it meets the following criteria: (1) technical aspect, such as operating in a strategic location; (2) marketing aspect, such as having a unique selling proposition that is not currently held by any competing products; (3) financial aspect, KAOSI has a business NPV value of IDR 4,158,829.4, an IRR value of 40,9%, a PP value of 1.79 years, and a PI value of 1.98, which indicates that this business is financially feasible. However, in terms of management and organization, only the management aspect can be met by KAOSI, its organizational structure is deemed impractical due to its management's extensive responsibilities.